Using Phase Change Materials in Cooled Storage Rooms (Damascus University Journal for engineering sciences, 2021)
The purpose of this paper is to decrease the usage of the electrical power in cooled storage rooms, and maintain an appropriate temperature during the power outage by using Phase Change Materials (PCM) in cooled storage of fruits and vegetables, where we designed and fabricated heat exchangers containing Water-Potassium Chloride solution as a phase change material, and applied it in a testing cooling chamber.Six experiments were done, where the PCM solidified at night, as the ambient temperature is low, and liquefied during the hours of high-power consumption, or power outage durations, taking advantage of the fusion latent heat. The ability of the proposed system was tested experimentally, and its capability was confirmed to maintain the chamber temperature below 2°C for 3 hours and a half.
Keywords: Heat Exchanger; Refrigeration Cycle; Phase Change Material; Coefficient of Performance